2012
DOI: 10.1002/pro.2155
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Plasmodium falciparum enoyl‐ACP reductase and implications on drug discovery

Abstract: Enoyl-acyl carrier protein reductase (ENR) is a crucial enzyme in the type II fatty acid synthesis pathway of many pathogens such as Plasmodium falciparum, the etiological agent of the most severe form of malaria. Because of its essential function of fatty acid double bond reduction and the absence of a human homologue, PfENR is an interesting drug target. Although extensive knowledge of the protein structure has been gathered over the last decade, comparatively little remains known about the dynamics of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…It is noteworthy that the extensive MD simulations conducted earlier on the PfENR-triclosan complex and its variants showed that the equilibration of all protein-ligand complexes occurred between 10 and 20 nanoseconds with a protein-RMSD value of 2.5 to 3.5 Å and a protein-RMSF value of less than 2.0 Å. 15 The results obtained in the present study were well within the benchmarked values reported earlier.…”
Section: Protein Backbone Stabilitysupporting
confidence: 89%
See 2 more Smart Citations
“…It is noteworthy that the extensive MD simulations conducted earlier on the PfENR-triclosan complex and its variants showed that the equilibration of all protein-ligand complexes occurred between 10 and 20 nanoseconds with a protein-RMSD value of 2.5 to 3.5 Å and a protein-RMSF value of less than 2.0 Å. 15 The results obtained in the present study were well within the benchmarked values reported earlier.…”
Section: Protein Backbone Stabilitysupporting
confidence: 89%
“…It is well documented in the literature that the PfENR protein attains stability between 10 and 20 nanoseconds of the simulation run. 15 Therefore, MD simulations of the 4 selected molecules along with the NAD-bound protein (ENR with cofactor only) were carried out for a duration of 20 nanoseconds. The stability of all the systems under investigation was evaluated by examining the RMSD and RMSF plots of both proteins and ligands.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive computational and experimental studies elucidating both the structural (27, 32) and dynamic (3438) nature of Pf ENR have been performed, with applications to drug discovery (3942). With the advancement in computational and experimental technology, we can rationally and efficiently screen for novel drugs with a higher hit rate than the traditional and more expensive high-throughput library screens.…”
Section: Introductionmentioning
confidence: 99%
“…First, the formation of a ternary ENR-NAD + -TCL complex stabilizes a normally flexible substrate-binding loop and is postulated to be the slowest step in the formation of the enzyme-inhibitor complex. 4549 Second, once bound, TCL is stabilized via π-stacking interactions between the TCL phenolic ring and the NAD + nicotinamide ring. 40 Indeed, kinetic studies have demonstrated that the IC 50 value of TCL improves with NAD + preincubation (i.e., TCL is an uncompetitive inhibitor with respect to varying NAD + concentrations).…”
Section: Resultsmentioning
confidence: 99%